Study of the effect of MAPP rate on the morphology and thermal properties of PP/r-PET blends - DAIRI, Badrina (Biopolymer Applications Journal, 2024)
The morphological and thermal study of the blends based on polypropylene (PP) and poly (ethylene terephthalate) recycled (r-PET) without and with a compatibilizer MAPP. PP/r-PET /MAPP Melt blending, the effect of blend composition of (r-PET) and MAPP was followed by morphological and thermal studies. The results obtained were discussed compared to the base polymer. In the absence of the compatibilizing agent (MAPP), PP/r-PET blends at different concentrations of r-PET exhibit clear phase separation with poor dispersion of r-PET in the PP matrix. The addition of MAPP in the blends PP/r-PET leads to a reduction of the particle size of the dispersed phase (r-PET) in the PP matrix, as well as improved interfacial conditions.